Peran Mediasi Kepuasan Kerja dalam Pengaruh Self-Efficacy dan Work-Life Balance terhadap Organizational Citizenship Behavior: Studi pada Karyawan PT Magnus Sedaya Selaras di Jakarta Barat - Mutiara Sifa Khairunisa; Zulvia Khalid (Jurnal Pajak dan Analisis Ekonomi Syariah, 2026)
This study aims to analyze the influence of Self-Efficacy and Work-Life Balance on Organizational Citizenship Behavior (OCB) with job satisfaction as a mediating variable in employees of PT Magnus Sedaya Selaras in West Jakarta. The study used a quantitative approach with a survey method of 98 employees selected using a saturated sample technique. Data analysis was carried out using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The variables used in this study include Self-Efficacy X1 and Work Life Balance X2 as independent variables, Organizational Citizenship Behavior dependent and job satisfaction (Z) as mediating variables. The type of research used includes primary and secondary where the primary is obtained directly by the researcher from the respondent or research subject related to the variable being studied, through the distribution of questionnaires to employees of PT Magnus Sedaya Selaras and secondary data obtained from other sources that have been available, such as documents, companies, organizational profiles and relevant literature. The results of the study showed that Self-Efficacy and Work-Life Balance had a positive and significant effect on job satisfaction, respectively. However, Self-Efficacy and Work-Life Balance did not have a significant effect directly on OCB. Job satisfaction has a positive and significant effect on OCB. In addition, job satisfaction has been shown to be able to significantly mediate the influence of Self-Efficacy and Work-Life Balance on OCB. These findings show that increasing OCB in PT Magnus Sedaya Selaras employees is more effectively done through increased job satisfaction driven by high Self-Efficacy and a good Work-Life Balance.